Analisis Kebutuhan Ruang Parkir Mall City Plaza Kabupaten Garut: Mall City Plaza Kabupaten Garut - Barokah, Maulana; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
Parking is one of the important components or aspects that cannot be separated from the needs of the transportation system. Along with the high number of people visiting, the existence of Mall City Plaza Garut also has a negative impact on the world of transportation, one of which is on parking space. During peak hours and when there are events, four-wheeled vehicles are often seen exceeding the capacity of the available parking space is not comparable to the volume of parking vehicles, so that unaccommodated vehicles can cause problems, such as parking on the roadside (on street) in front of Mall City Plaza Garut.This study aims to determine the parking space requirements (static and dynamic capacity) at Mall City Plaza Garut Regency. This study uses a quantitative method with descriptive analysis, conducted directly in the field by collecting primary and secondary data. Primary data was obtained from direct observations in the field, including the area of parking space, parking vehicle volume, parking duration, and parking patterns, while secondary data was obtained from the floor plan of Mall City Plaza Garut Regency. Based on the data analysis and discussion, it can be concluded that the maximum accumulation of off-street parking is 330 motorcycles and 177 cars, while on-street parking is 58 motorcycles and 21 cars. The volume of off-street parking is 1,116 motorcycles and 664 cars, while on-street parking is 181 motorcycles and 21 cars. The duration of off-street parking for motorcycles is 123 minutes and for cars 128 minutes, while for on-street parking it is 86 minutes for motorcycles and 75 minutes for cars. The largest off-street parking index for motorcycles is 100.00% and for cars 103.39%, while for on-street parking it is 98.15% for motorcycles and 87.50% for cars. The static capacity for off-street parking is 331 for motorcycles and 177 for cars, while for on-street parking it is 54 for motorcycles and 24 for cars. The largest dynamic off-street parking capacity for motorcycles occurs on Wednesdays at 1588.80 and the smallest on Thursdays at 960.97. The largest dynamic parking capacity for cars occurs on Mondays at 685.16 and the smallest on Tuesdays at 497.81. The largest dynamic capacity for on-street motorcycle parking occurred on Friday at 2482.50 and the smallest on Sunday at 1385.58. The largest dynamic capacity for car parking occurred on Monday at 1385.22 and the smallest on Saturday at 849.60. The demand for off-street parking space for motorcycles has been met, while the calculated demand for off-street parking space for cars is 204 SRP. Therefore, the available parking space cannot meet the demand, and additional parking space is needed to serve visitors to Mall City Plaza in Garut Regency. The demand for on-street parking space for motorcycles and cars has been met with the available capacity. Keywords: Parking space requirement, Static Capacity, Dynamic Capacity